A monoclonal antibody against glycoproteins of Aspergillus fumigatus shows anti-adhesive potential. (February 2015) - Kumar, Awanit; Shukla, P.K.
Abstract: There has been an increase in the cases of fungal resistance against many antifungal drugs and an effective alternative mode in the form of immunotherapy is being considered as new hope. The adhesion of Aspergillus fumigatus conidia to the host components is one of the prime factors to cause aspergillosis. Carbohydrate components or glycoproteins present on the cell surface play an important role in interaction of the organism to the host and leads to adhesion. Any substance which is capable of disrupting this interaction may be a vital tool for the fungal clearance and hence may protect the host from infections caused by the fungus. In this study, a murine monoclonal antibody IgM generated against the secretory antigens of A. fumigatus, was found to be specific to a common epitope containing glyco-moieties of the various proteins and exhibited anti-adhesive potential in vitro . Graphical abstract: Highlights: Cell surface carbohydrate components have role in fungal adhesion to the host. Generation of a mouse monoclonal antibody (MAb) against A. fumigatus glycoproteins. Assessment of the anti-adhesive potential of the MAb against A. fumigatus conidia.